2020
DOI: 10.3390/electronics9050805
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Object Detection for Electric Vehicle Wireless Charging

Abstract: Wireless power transfer technology is being widely used in electric vehicle wireless-charging applications, and foreign object detection (FOD) is an important module that is needed to satisfy the transmission and safety requirements. FOD mostly includes two key parts: metal object detection (MOD) and living object detection (LOD), which should be implemented during the charging process. In this paper, equivalent circuit models of a metal object and a living object are proposed, and the FOD methods are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 95 publications
0
24
0
1
Order By: Relevance
“…Detection methods based on the coupling effect with auxiliary circuit have effective detection sensitivity compared to other detection methods. The Table 17 shows sensors and related detection parameters being used in the FOD [238] Among them the active detection methods are implemented before or during charging being suitable for both MOD and LOD. The passive detection techniques are appropriate for MOD and can only be executed while charging.…”
Section: Living Object Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection methods based on the coupling effect with auxiliary circuit have effective detection sensitivity compared to other detection methods. The Table 17 shows sensors and related detection parameters being used in the FOD [238] Among them the active detection methods are implemented before or during charging being suitable for both MOD and LOD. The passive detection techniques are appropriate for MOD and can only be executed while charging.…”
Section: Living Object Detection Methodsmentioning
confidence: 99%
“…However, sensitivity effective than the other methods. The advantages and disadvantages of the detection methods are categorized in Table 18 [238] The authors in [239], suggested research areas for development of FOD: (a) combination of two different detection methods would improve the sensitivity, accuracy, signal-to-noise ratio, and object localization, (b) A method that can detect both living and metal objects simultaneously are not influenced by environment and conductive materials, (c) The EMI/EMC issues in FOD detection, and (d) automatically removing foreign objects without human intervention.…”
Section: Living Object Detection Methodsmentioning
confidence: 99%
“…or have discussed the reduction of efficiency and quality factor at fixed operating frequencies [5][6][7][8][9]. In addition to enabling power transmission in systems with fixed obstacles, it is also important to restore the system's output and transmission efficiency when an unknown obstacle is suddenly located [10][11][12]. Due to the characteristics of the MRWPT operating at the resonant frequency, the influence of the obstacle will show various aspects according to its electrical/magnetic properties, but the effect of these properties on the resonant frequency or output power has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the United States (U.S.) Department of Energy (DOE) and the Society of Automotive Engineers (SAE) led the wireless power transfer and alignment task force and began research and standardization of WPT technology [8]. Researchers from major automotive manufacturers and charging infrastructure suppliers [9] wished to develop WPT technology suitable for EVs while participating in the EV WPT standardization. The primary goal of the development of WPT for the EVs in its early stages was to ensure the safety of users during the implementation of WPT and maximizing the charging efficiency of wireless charging.…”
Section: Introductionmentioning
confidence: 99%